Reduced regulatory T cells with increased proinflammatory response in patients with schizophrenia - AKKOÇ, TUNÇ (SPRINGER, 2020)
Aim To investigate whether circulating T cells including regulatory T cells (Treg) and derived cytokines contribute to the immune imbalance observed in schizophrenia. Methods Forty patients with schizophrenia and 40 age, sex, body mass index, education, and smoking status-matched healthy controls (HC) are included in the study. We stained cells with anti-CD14, anti-CD3, anti-CD4, anti-CD8, anti-CD19, anti-CD20, and anti-CD16/56. Peripheral blood mononuclear cells (PBMCs) were isolated and stained with the human FoxP3 kit containing anti-CD4/anti-CD25 and intracellular anti-Foxp3. PBMCs were cultured for 72 h and stimulated with anti-CD3/anti-CD28. Cytokines (IL-2, IL-4, IL-6, IL-10, IFN-gamma, TNF-alpha, and IL-17A) were measured from the culture supernatant and plasma using the Th1/Th2/Th17 cytokine bead array kit. Results In comparison with HC, Treg percentages in schizophrenia were higher (1.17 +/- 0.63 vs 0.81 +/- 0.53, P = 0.005) in unstimulated but lower in the stimulated condition (0.73 +/- 0.69 vs 0.97 +/- 0.55, P = 0.011). Activated T cell percentages were higher in schizophrenia than HC in unstimulated (2.22 +/- 0.78 vs 1.64 +/- 0.89, P = 0.001) and stimulated (2.25 +/- 1.01 vs 1.72 +/- 1.00, P = 0.010) conditions. The culture supernatant levels of IL-6 (7505.17 +/- 5170.07 vs 1787.81 +/- 1363.32, P < 0.001), IL-17A (191.73 +/- 212.49 vs 46.43 +/- 23.99, P < 0.001), TNF-alpha (1557 +/- 1059.69 vs 426.57 +/- 174.62, P = 0.023), and IFN-gamma (3204.13 +/- 1397.06 vs 447.79 +/- 270.13, P < 0.001); and plasma levels of IL-6 (3.83 +/- 3.41vs 1.89 +/- 1.14, P = 0.003) and IL-17A (1.20 +/- 0.84 vs 0.83 +/- 0.53, P = 0.033) were higher in patients with schizophrenia than HC. Conclusion Our explorative study shows reduced level of Foxp3 expressing Treg in a stimulated condition with induced levels of proinflammatory cytokines in patients with schizophrenia.
Keywords: Schizophrenia; Regulatory T cell; FoxP3; IL-17A; Adaptive immunity; T cell; 1ST EPISODE; DRUG-NAIVE; GENE-EXPRESSION; CYTOKINE; LYMPHOCYTES; BLOOD; DOPAMINE; PATHWAY; SERUM; METAANALYSIS